Factors Affecting Emotional Maturity in Adolescents of High School - Iroma Maulida; Candra Andodo; Ulfatul Latifah (Indonesian Journal of Global Health Research, 2025)
Class XII adolescents are usually preoccupied with learning in preparation for their graduation exams and college entrance exams. These hectic activities can cause aggravation if adolescents cannot deal with them well. Deep aggravation can lead to emotions. Emotional maturity is very important for adolescents in dealing with a problem. Therefore, the purpose of this study was to determine the factors that influence the emotional maturity of adolescents at SMU N 2 Tegal Regency. This research was an observational analytic study with cross sectional design. The study population was class XII MIPA students totaling 178 and a sample of 51 students was taken by cluster sampling. Data were collected using a questionnaire to measure emotional maturity and its causative factors including self-acceptance, interaction with peers, environmental assessment of adolescents and adolescent parenting. Data were analyzed univariately and bivariately. The results showed that there was a relationship between self-acceptance attitude and emotional maturity with a pvalue: 0.038 and OR: 8.7. The percentage of students with an attitude of accepting themselves has a good emotional maturity that is more than the percentage of students who have an attitude of not accepting themselves. But there is no relationship between interaction with peers (pvalue: 0.276), assessment of the adolescent environment (pvalue: 0.657) and adolescent parenting (pvalue: 0.352) to emotional maturity. It can be concluded that the attitude of acceptance in adolescents affects the emotional maturity of adolescents so that efforts need to be made by schools and parents to improve the attitude of adolescent acceptance.